The integrated properties of the molecular clouds from the JCMT CO(3–2) High-Resolution Survey. Issue 4 (3rd December 2018) - Colombo, D; Rosolowsky, E; Duarte-Cabral, A; Ginsburg, A; Glenn, J; Zetterlund, E; Hernandez, A K; Dempsey, J; Currie, M J
ABSTRACT: We define the molecular cloud properties of the Milky Way first quadrant using data from the JCMT CO(3–2) High-Resolution Survey. We apply the Spectral Clustering for Interstellar Molecular Emission Segmentation (SCIMES) algorithm to extract objects from the full-resolution data set, creating the first catalogue of molecular clouds with a large dynamic range in spatial scale. We identify more than 85000 clouds with two clear sub-samples: ∼35500 well-resolved objects and ∼540 clouds with well-defined distance estimations. Only 35 per cent of the catalogued clouds (as well as the total flux encompassed by them) appear enclosed within the Milky Way spiral arms. The scaling relationships between clouds with known distances are comparable to the characteristics of the clouds identified in previous surveys. However, these relations between integrated properties, especially from the full catalogue, show a large intrinsic scatter (∼0.5 dex), comparable to other cloud catalogues of the Milky Way and nearby galaxies. The mass distribution of molecular clouds follows a truncated-power-law relationship over three orders of magnitude in mass with a form d N /d M ∝ M −1.7 with a clearly defined truncation at an upper mass of$M_0 \sim 3 × 10^6\, M_\odot$, consistent with theoretical models of cloud formation controlled by stellar feedback and shear. Similarly, the cloud population shows a power-law distribution of size with d N /d R ∝ R −2.8 with a truncation at R 0 = 70 pc.